The Dilemma of Context - Scharfstein, Ben-Ami (NYU Press, 1989)
In The Dilemma of Context, Scharfstein contends that the problems encountered with context are insoluble. He explains why this problem lays an intellectual burden on us that, while remaining inescapable,can become so heavy it destroys the understandingit was created to further.